Complementary and Alternative Drugs Use among Preoperative Patients: A Cross-Sectional Study in Italy. (21st July 2011) - Lucenteforte, Ersilia; Gallo, Eugenia; Pugi, Alessandra; Giommoni, Federica; Paoletti, Angelica; Vietri, Michele; Lupi, Patrizia; La Torre, Maristella; Diddi, Gianluca; Firenzuoli, Fabio; Mugelli, Alessandro; Vannacci, Alfredo; et al.
Abstract : Complementary and alternative drugs (CADs) are widely used in preoperative patients and may lead to potential interactions and adverse reactions. The aim of our study is to evaluate the prevalence and the predictors of CADs use among preoperative patients using data from an Italian survey. This cross-sectional study, which enrolled 478 patients (response rate: 83.5%), was carried out in three Tuscany hospitals (Italy). The prevalence of CADs use was 49.8%: 233 out of 238 participants used herbal products and/or dietary supplements. Valeriana officinalis was the most reported product (19.4%). According to univariate analysis, users were commonly identified among middle-aged or older patients; unadjusted ORs were 2.1 (95% CI: 1.3–3.3) for patients aged 48–69 years, and 3.0 (95% CI: 1.9–4.7) for those of 70–95 years, when compared with individuals aged 18–47 years. Except for education and gender, adjusted estimates showed consistent results with univariate analyses: direct association was observed with higher education, and—although not significantly—with female gender. The high prevalence of CAD use in preoperative period could be suggestive of a certain risk of adverse effects due to CADs interactions. A careful medical history of CADs consumption should be ascertained before surgery.